THE EFFECT OF OPERATIONAL RISK MANAGEMENT PRACTICES ON THE FINANCIAL PERFORMANCE IN COMMERCIAL BANKS IN TANZANIA - Meshack, Kerongo Maatwa; Mwaura, Rose Wairimu (American Journal of Finance, 2016)
Purpose: The purpose of the study was to determine the effect of operational risk management practices on the financial performance in commercial banks in Tanzania Methodology: The research problem was studied by use of a descriptive research design. The population of the study consisted of all commercial banks in Tanzania. The study used the sample size of 34 commercial banks in Tanzania. Therefore all the commercial banks participated in equally. Questionnaires were the primary data collection tool in this study. The data gathered from the respondents shall be analyzed and presented using descriptive statistics. Results: The study found that the three independent variables in the study credit risk, Insolvency risk and Operational efficiency influenced the financial performance for the period under study. Credit risk Insolvency risk and Operational efficiency influenced commercial banks financial performance for the period of study. Unique contribution to theory, practice and policy: This study therefore recommends that the commercial banks should handle their operations appropriately as the changes in the factors like Insolvency and Credit risk bring about an effect on the profitability of commercial banks hence affecting their financial performance